Analisis Penerapan Model Project Based Learning Berbasis Etnosains pada Pembelajaran IPA di Sekolah Dasar - Yulia, Nurul Mahruzah; Salsabila, Ananda Dwi; Anggita, Audiya Lutfi Ilma (Madrasah Ibtidaiyah Education Journal, 2025)
(PJBL) integrated with ethnoscience in Natural Science (IPA) learning in Elementary Schools. The ethnoscience approach is used as a framework to connect scientific concepts with local wisdom and culture, so that learning becomes contextual, meaningful, and relevant for students. This study uses a descriptive qualitative method with data collection through teacher interviews, analysis of learning documents, and classroom observations. The research subjects consisted of teachers and students at MI Nurul Huda Jelu and MI Abu Dzarrin, Bojonegoro City. The results show that the integration of PJBL and ethnoscience improves students' understanding of science concepts, critical thinking skills, creativity, and affective engagement. Students are able to connect scientific phenomena with local cultural practices, such as processing traditional medicinal plants and observing local agricultural activities. However, the study also found challenges, including limited local culture-based learning resources, teacher competency, and supporting infrastructure. Suggested strengthening strategies include the development of local wisdom-based teaching materials, teacher professional training, the use of technology and media, and collaboration with the local community. Overall, PJBL-ethnoscience has proven to be effective as a learning model that not only improves scientific competence but also instills an appreciation for local culture and shapes the character of students, so that the findings of this study are expected to be a reference in developing science learning that is relevant, contextual, and oriented towards cultural preservation in Elementary School